The Pathogenic Triad of Chronic Cough: Postnasal Drip Syndrome, Asthma, and Gastroesophageal Reflux Disease - Wulyo Rajabto; Ari Fahrial Syam; Heru Sundaru (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2007)
Chronic cough, lasting for 3 weeks or more, is one of the most common symptoms for which adult patients seek medical attention. The pathogenic triad of chronic cough is Postnasal Drip Syndrome (PNDS), Asthma, and Gastroesophageal Reflux Diseases (GERD) are the vast majority etiology of chronic cough in non-smoker adult with normal chest X-ray. The clinical investigations that should be performed are spirometry pre-post bronchodilator and bronchoprovocation testing for asthma; plain sinus radiograph and or computed tomographic imaging of the sinus for PNDS due to sinusitis; gastro-intestinal investigation 24 hours oesophageal pH monitoring and upper gastrointestinal endoscopy for GERD.   Keywords: chronic cough, postnasal drip syndrome, asthma, gastroesophageal reflux disease